Pengaruh Good Coorporate Governance dan Enterprise Risk Management terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdarftar di BEI Tahun 2020-2021 - Halizah, Putri Nur; Suwarno, Suwarno (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of Good Corporate Governance and Enterprise Risk Management on firm value in manufacturing companies listed on the Indonesia Stock Exchange. using 350 samples of financial statements. This test uses the Smart PLS analysis tool. The results of the analysis show that management ownership and audit committee affect firm value, while institutional ownership, independent commissioners and ERM have no effect on firm value. Keywords: Managerial Ownership; Institutional Ownership; Independent Commissioner; Audit Committee; ERM; Firm Value